Lolita - Nabokov, Vladimir Vladimirovich 1899-1977. (New York Vintage, 1997)
The most controversial classic novel of the 20th century, Lolita tells the story of Humbert Humbert, a middle-aged man who is aroused to erotic desire only by a young girl. Awe and exhilaration--along with heartbreak and mordant wit--abound in Lolita, Nabokov's most famous and controversial novel, which tells the story of the aging Humbert Humbert's obsessive, devouring, and doomed passion for the nymphet Dolores Haze. Lolita is also the story of a hypercivilized European colliding with the cheerful barbarism of postwar America. Most of all, it is a meditation on love--love as outrage and hallucination, madness and transformation.
"50th anniversary edition"--Cover.
UCWS-2014-G-1610 donated by Prof. Nathalie Africa-Verceles
Keywords: Child molesters -- Fiction; Russian fiction -- 20th century -- Translations into English; Teenage girls -- Sexual behavior -- Fiction; Pedophilia -- Fiction; Middle-aged men -- Fiction; Erotic fiction; Love stories